2019
DOI: 10.1177/1464884919870329
|View full text |Cite
|
Sign up to set email alerts
|

Mediatization of conflict in the social media era: A case study of Sino-Indian border crisis in 2017

Abstract: Inspired by the concepts of Arrested War and actor–network theory, this study has traced and analyzed four main actors in the wars and conflicts in the social media age: social media platform, the mainstream news organizations, online users, and social media content. These four human and nonhuman actors associate, interact, and negotiate with each other in the social media network surrounding specific issues. Based on the case study of Sino-Indian border crisis in 2017, the central argument is that social medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…It was found that there are limited. This study has used 'arrested conflict' approach that deals with the third phase of mediatization explained by Zhang (2019). This approach highlights the traditional/professional media's use of social media for the conflict coverage.…”
Section: Theoretical and Methodological Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that there are limited. This study has used 'arrested conflict' approach that deals with the third phase of mediatization explained by Zhang (2019). This approach highlights the traditional/professional media's use of social media for the conflict coverage.…”
Section: Theoretical and Methodological Approachmentioning
confidence: 99%
“…In the first phase, the media reporting of conflicts was one-way and centralized unlike the second phase which was more decentralized with multiple sources of information. However, Zhang (2019) quoting the study of Hoskins and O'Loughlin noted the third phase of mediatization of conflicts called 'arrested conflict' that highlights the traditional/professional media's use of social media for the conflict coverage (Zhang, 2019, p. 3). Zhang argues that social media plays enabling role in contemporary conflicts and wars while traditional news organizations and audience employ functionalities to set and counter-set the public agenda (p. 15).…”
Section: Use Of Social Media By Traditional News Organizationsmentioning
confidence: 99%
“…Mediatisation theory has been widely applied in studying the dynamics between media and society, especially in relation to politics, claiming that media has become an independent social institution that has its own logic and can challenge the logic of other social institutions (Hjarvard, 2008;Mazzoleni, 2017;Mazzoleni & Schulz, 1999;Str€ omb€ ack, 2008). This concept has also been used to discuss the interaction between digital media and political transformation in China (Sun, 2007;Sun, 2014;Meng, 2016;Zhang, 2019;Wang, 2020). Follow this path, the author explores how Chinese DV as a justice-seeking activity is mediatised based on three signals of mediatisation in the context of social media platforms concluded by Hjarvard ( 2014): (i) the platform has created public spheres for other social institutions, thus become the connecting node between them; (ii) its logic accommodates, as well as challenges the logics of other social institutions, thus become an integral part of them; (iii) (social)media-related personnel and processes became part of the organisational changes in other social institutions.…”
Section: Mediatised Justice-seeking: Media Logic and DV Practicesmentioning
confidence: 99%
“…However, the notable decrease in government subsidies since the 1990s has created large numbers of state-owned, yet market-oriented, media (Huang, 2016). These market-oriented media, which often share a similar, sensational journalistic practice with the tabloid press in the West, are more popular with the general public than their propaganda-oriented counterparts (Zhang, 2019). Focusing on the market-oriented media, Zhang (2013) conducted a textual analysis of Henan-related news coverage.…”
Section: Literature Reviewmentioning
confidence: 99%